High‐Throughput Screening of Anti‐cancer Drugs Using a Microfluidic Spheroid Culture Device with a Concentration Gradient Generator. Issue 9 (6th September 2022) - Lee, Yugyeong; Chen, Zhenzhong; Lim, Wanyoung; Cho, Hansang; Park, Sungsu
Abstract: Tumor spheroid models are widely used for drug screening as in vitro models of the tumor microenvironment. There are various ways in which tumor spheroid models can be prepared, including the self‐assembly of cells using low‐adherent plates, micro‐patterned plates, or hanging‐drop plates. Recently, drug high‐throughput screening (HTS) approaches have incorporated the use of these culture systems. These HTS culture systems, however, require complicated equipment, such as robot arms, detectors, and software for handling solutions and data processing. Here, we describe protocols that allow tumor spheroids to be tested with different concentrations of a drug in a parallel fashion using a microfluidic device that generates a gradient of anti‐cancer drugs. This microfluidic spheroid culture device with a concentration gradient generator (μFSCD‐CGG) enables the formation of 50 tumor spheroids and the testing of drugs at five different concentrations. First, we provide a protocol for the fabrication of the μFSCD‐CGG, which has both a culture array in which tumor cells are injected and aggregate to form spheroids and a concentration gradient generator for drug testing. Second, we provide a protocol for tumor spheroid formation and HTS of anti‐cancer drugs using the device. Finally, we provide a protocol for assessing the response of tumor spheroids at different drug concentrations. To address the needs of the pharmaceutical industry, this protocol can be used for various cell types, including stem cells, and the number of tumor spheroids and drug concentration ranges that can be tested in the μFSCD‐CGG can be increased. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Fabrication of a microfluidic spheroid culture device with a concentration gradient generator (μFSCD‐CGG) Basic Protocol 2 : Seeding cells and formation of spheroids in the μFSCD‐CGG Basic Protocol 3 : Drug treatment and assessment of cell viability in the μFSCD‐CGG